A Review Based on Young Adult Consumers' Perspective: What Should McCafe Indonesia Do? - Lawrance, Lawrance; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2013)
Coffee Café Shop industry continued to show a positive trend. This case evidenced with the increasing number of players in the industry, it is not limited only for multinationals but also small local players. But, seems the coffee café companies still focus to target relatively similar consumers. Can be said that the market leader, Starbucks, has major influence on how competitors act. McCafe Indonesia, which is an initiative coffee cafe from McDonald's, will become an interesting research object considering its mother brand effect. Should McCafe targets similar consumers to Starbucks or other white space potential? Therefore, the authors are interested in doing research to map out how the consumers of coffee cafes in Indonesia today. Through a market mapping, hopefully new segment could be explored by McCafe. Keywords:Segmentation, Positioning, McCafe, Starbucks, J.Co